1995
DOI: 10.1016/1381-1169(94)00036-0
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in hydrodehalogenation of polychloro- and polybromobenzenes under multiphase conditions

Abstract: The competitive hydrodehalogenation of isomeric o-, m-and p-dichloro (and dibromo) benzenes with Hz at atmospheric pressure and Pd/C or Ni-Raney carried out in a multiphase system (organic solvent and 50% KOH aq. solution) is influenced by the presence of a bulky quatemary onium salt where both the catalytic activity and the selectivity change in relation to the halogen to be removed and the metal catalyst used. In particular, the Ni-Raney catalyst becomes effective in the reduction only if an onium salt is ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 8 publications
5
44
0
Order By: Relevance
“…It can be used to efficiently remove aromatic halogens (from toxic compounds such as PCBs and PCDD/PCDFs) [13][14][15][16][17], or to reduce aromatic carbonyls [18][19][20][21], simply by tuning the conditions. The multiphase system consists of a hydrocarbon solvent, an aqueous phase, a phase-transfer (PT) agent, a supported metal catalyst, hydrogen at atmospheric pressure, at low temperature (T < 50 • C).…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to efficiently remove aromatic halogens (from toxic compounds such as PCBs and PCDD/PCDFs) [13][14][15][16][17], or to reduce aromatic carbonyls [18][19][20][21], simply by tuning the conditions. The multiphase system consists of a hydrocarbon solvent, an aqueous phase, a phase-transfer (PT) agent, a supported metal catalyst, hydrogen at atmospheric pressure, at low temperature (T < 50 • C).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had indicated that Pd/C is a more active reduction catalyst than Raney-Ni under multiphase conditions for the hydrodechlorination of chlorobenzenes, 5 while RaneyNi is more active, provided A336 is present, in the hydrodebromination of bromobenzenes. 5 The observed activity of the Raney-Ni/A336 multiphase system for the hydrogenolysis of benzyl ethers, and the opposite behavior of Pd/C, is another case of changes in the chemoselectivity produced by modifications of a component of the catalytic multiphase system (in this case the catalyst).…”
Section: This Journal Is © the Royal Society Of Chemistry 2002mentioning
confidence: 99%
“…Pd/C, Pt/C) allows a variety of reduction reactions to be conducted under mild conditions (T = 50°C, pH 2 = 1 atm), e.g. ; hydrodehalogenation of aryl halides, [2][3][4][5][6] hydrogenation of carbonyls, 7 hydrogenolysis of hydroxyls, 7 up to aromatic hydrogenation. 7,8 For substrates liable to multiple reductions, selectivity can be achieved by tuning the multiphase system, in order to favor one over the other of the possible reaction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…And-contrary to Pd/C that showed activity in the absence of A336 as well-functioned only when A336 was present. 78,79 Platinum on charcoal provided a further means for directing the selectivity of the multiphasic hydrodehalogenation reactions. For example, the same reaction of Fig.…”
Section: Hydrodehalogenationmentioning
confidence: 99%
“…[76][77][78][79]81,82 This reaction was investigated from the kinetic standpoint, using kinetic models that allowed an accurate analysis of the reaction selectivity. 83 In particular it was shown that halogen removal was accelerated with respect to carbonyl reduction in the presence of A336.…”
Section: Reductionmentioning
confidence: 99%